2021
DOI: 10.1111/jpm.12781
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence and risk factors for PTSD among psychiatric nurses: Systematic review and directions for future research and practice

Abstract: What is known on the subject?• Trauma among psychiatric nurses and other healthcare workers is related to workplace violence, but other risk factors may also contribute, including those occurring before, during or after workplace violence. What does this paper add to existing knowledge?• Most previously identified PTSD risk factors were not tested or supported in research with psychiatric nurses, although there is promising evidence for risk factors including severe or injurious assault, cumulative exposure, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…In addition, due to the increasing demand of mental health services in China, psychiatrists are facing an inflow of patients suffering from mental illness, which would increase their workload. Hospitalizations in psychiatric settings maybe for days, weeks, or longer, and this ongoing care relationship may also increase the incidence of WPV ( 41 43 ). The prevalence of WPV vary across socio-economic groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the increasing demand of mental health services in China, psychiatrists are facing an inflow of patients suffering from mental illness, which would increase their workload. Hospitalizations in psychiatric settings maybe for days, weeks, or longer, and this ongoing care relationship may also increase the incidence of WPV ( 41 43 ). The prevalence of WPV vary across socio-economic groups.…”
Section: Discussionmentioning
confidence: 99%
“…burnout, workplace support). Hilton et al (2021) concluded that there is no strong evidence base for choosing risk factors to target for PTSD prevention in this occupational group. In order to address this complex aetiology, interventions which provide support across time (before, during and after the event) and which include both one‐on‐one support and systemic workplace policy changes may be most impactful.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review (Hilton et al, 2021) investigated evidence for risk factors for PTSD among nurses in psychiatric settings occurring before the traumatic event (e.g. nurses’ gender, training), during the event (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If burnout mediates the association between workplace exposures and PTSD, then workplace programmes to reduce burnout could be a helpful component of efforts to prevent workplace PTSD. If instead critical events have only a direct relation to PTSD symptoms, then more efforts could be placed on preventing workplace exposures, monitoring for posttraumatic symptoms, and providing PTSD-specific interventions when needed (Hilton et al 2021). The present study was conducted to address this gap by examining the role of burnout in the relationships among critical events, chronic stressors, worklife incongruence, and PTSD symptoms among psychiatric workers.…”
Section: The Role Of Burnout In Ptsd In Healthcare Workersmentioning
confidence: 99%